Ida Tarbell : portrait of a muckraker - Brady, Kathleen (University of Pittsburgh Press, 1989)
Epitomizes the achieving woman who is not a feminist. Her generation called her a "muckraker," but in our time she would have been known as "an investigative reporter." She achieved more than almost any woman of her generation, but she was an antisuffragist, believing that the traditional roles of wife and mother were more important than public life.